Post Ankle Sprain Injury Associated with Lateral Ligaments Tear Rehab Protocol - Alghalibi, Mohammed Thamer; Alghamdi, Abdulrahman Saleh; Alosaimi, Fawaz Sulayyih Hamad (International Journal of Innovative Research in Medical Science, 2022)
Introduction: Injury to the lower extremity joint injury is one of the most common consequences of accidents in recreation and sports. The incidence of ankle sprain after or during the rehabilitation of lateral ligament tear is popular however, little is known about the prevalence of post rehabilitation ankle sprain in Saudi Arabia. Therefore, the aim of this study was to assess the prevalence of post ankle sprain injury among patients who underwent lateral ligament tear rehab conservatively. Methodology: This is a cross sectional study among patients who underwent lateral ligament tear rehabilitation conservatively using self-reported questionnaire which was distributed using online means as WhatsApp or Facebook throughout Google sheets. The data was analyzed using the statistical package for the social science (SPSS) version 23.0. Results: In this study, we were able to collect data from 104 participants who applied to the inclusion criteria. Among the participants 43.3 % of the participants aged between 20 -30 years old and 70.2 % of the participants were males and 69.2 % were married. According to the participants, 16.3 % of the participants reported having ankle sprain injury after or during the rehabilitation while 6.7 % of them reported having ankle sprain injury during the rehabilitation. Conclusion: We found that 16.3 % of the patients reported having ankle sprain injury after or during the lateral ligament injuries rehabilitation. Patients reported full recovery after rehabilitation showed lower prevalence of post rehabilitation ankle sprain injury.